2003
DOI: 10.4049/jimmunol.170.6.3254
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Macrophage Recruitment, Proliferation, and Activation in Colony-Stimulating Factor-1-Deficient Mice Results in Decreased Tubular Apoptosis During Renal Inflammation

Abstract: Kidney tubular epithelial cell (TEC) death may be dependent on the number and activation state of macrophages (Mφ) during inflammation. Our prior studies indicate that activated Mφ release soluble mediators that incite TEC death, and reducing intrarenal Mφ during kidney disease diminishes TEC apoptosis. CSF-1 is required for Mφ proliferation and survival. We hypothesized that in the absence of CSF-1, Mφ-mediated TEC apoptosis would be prevented during renal inflammation. To test this hypothesis, we evaluated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 68 publications
5
97
0
Order By: Relevance
“…Furthermore, we found that apoptosis is strongly correlated with renal disease severity in MRL/lpr mice, supporting the relevance of apoptosis to lupus nephritis. The striking correlation with monocyte/macrophage numbers (r=0.951) is particularly interesting, and is in keeping with the observations of Lenda et al [51,52], in which macrophage-directed apoptosis appears to be relevant in models of progressive tubulointerstitial damage, such as obstructive nephropathy, and in these same MRL/lpr mice.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, we found that apoptosis is strongly correlated with renal disease severity in MRL/lpr mice, supporting the relevance of apoptosis to lupus nephritis. The striking correlation with monocyte/macrophage numbers (r=0.951) is particularly interesting, and is in keeping with the observations of Lenda et al [51,52], in which macrophage-directed apoptosis appears to be relevant in models of progressive tubulointerstitial damage, such as obstructive nephropathy, and in these same MRL/lpr mice.…”
Section: Discussionsupporting
confidence: 69%
“…To answer this question, we analyzed the accumulation and activation of M, as well as M-mediated TEC apoptosis during renal inflammation induced by UUO. We compared TgC/ϩ and WT kidneys 3 days after UUO, since at this time intrarenal M accumulation is florid and hydronephrosis is less severe as compared with later time points (12). Consistent with previous findings, we detected twice the numbers of M accumulated in WT-obstructed kidneys (interstitium, glomeruli) as compared with Csf1 op /Csf1 op -obstructed kidneys (Fig.…”
Section: Tgc Expression Restores Renal Inflammation In Csf-1-deficiensupporting
confidence: 78%
“…Furthermore, CSF-1-deficient MRL-Fas lpr mice are protected from nephritis and the systemic illness characteristic of the MRLFas lpr wild-type (WT) strain (8). Similarly, in unilateral ureteral obstruction (UUO) in which blocking the flow of urine results in a florid M infiltration into the renal interstitium that leads to tubular damage and interstitial fibrosis (9 -11), we determined that renal injury is dependent on CSF-1 (12). In the CSF-1 null mice, fewer M accumulate within the kidney, and moreover, they do not proliferate and fewer are activated than in WT mice.…”
Section: Acrophage (M)mentioning
confidence: 99%
“…42 We collected 0.5 ϫ 10 6 to 1.0 ϫ 10 6 total kidney cells and 0.5 ϫ 10 5 to 1.0 ϫ 10 5 blood leukocytes/BM Mo using a FACSCalibur (Becton Dickinson, San Jose, CA) and analyzed the data using Flowjo software (Tree Star, Palo Alto, CA). The BM Mo and circulating Mo were characterized by gating on the SSC low CD11b high population.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…9,10 Moreover, CSF-1-deficient mice (Csf1 op/op ;MRL-Fas lpr ) are protected from kidney disease and systemic illness. 11,12 However, the Csf1 op/op ;MRLFas lpr mice are frail and have skeletal abnormalities and numerous other defects. [13][14][15][16] Thus, it is possible that the effect of deleting CSF-1 on lupus in MRL-Fas lpr mice is, at least in part, not directly related to the reduction of Mø.…”
Section: Introductionmentioning
confidence: 99%